Natural superficial water storage and aquifer recharge assessment in Brazilian savanna wetland using unmanned aerial vehicle and geophysical survey - Furlan, Lucas Moreira [UNESP]; Rosolen, Vania [UNESP]; Salles, Jepherson; Moreira, César Augusto [UNESP]; Ferreira, Manuel Eduardo; Bueno, Guilherme Taitson; De Sousa Coelho, Carla Vanessa [UNESP]; Mounier, Stéphane (Canadian Science Publishing, 2020)
Human pressure on the water resources provided by natural isolated wetlands has intensified in Brazil due to an increase in agricultural land equipped with irrigation. However, the amount of water stored in these areas and its contribution to aquifer recharge is unknown. This study aimed to quantify the amount of water that can be retained in a natural wetland and to propose a model of groundwater recharge. We used remote sensing techniques involving unmanned aerial vehicle to map the wetland and highlight its internal morphology, using a red-green-blue orthomosaic and a digital surface model. The 2-D inversion and a pseudo-3-D model from electrical resistivity tomography data were used to visualize the subsurface structures and hydrologic flow paths. The wetland is a reservoir storing up to 416.996 m3 of water during the rainy months. Distinct internal compartments characterize the wetland topography and different water-volume storage, lower in the border and higher in the center. A leakage point connects surface water to groundwater through direct vertical flow, which constitutes the aquifer recharge zone. Remotely sensed very high-resolution images allied with geophysical techniques allowed complete surface and subsurface imaging and offered visual tools that contributed to understanding the hydrodynamics of the wetland.
Keywords: Aerial photogrammetry; Hydrodynamics; Hydropedology; Resistivity; Tropical wetlands; Water resources